Improving DC-Link Capacitor Lifetime for Three-Level Photovoltaic Hybrid Active NPC Inverters in Full Modulation Index Range - Kim, Ye Ji; Kim, Seok Min; Lee, Kyo Beum (IEEE Transactions on Power Electronics, 2021)
This article presents a dc-link capacitor lifetime improvement method for three-level photovoltaic hybrid active neutral-point clamped inverters in full modulation index range. The capacitors are one of the components with vulnerable reliability in a power conversion system. The dc-link capacitor current ripples lead to temperature rise and wear-out failure of the capacitors. The accumulated thermo-mechanical damages from the temperature rise reduce the capacitor lifetime and reliability of the system. The proposed modulation method suppresses effectively the dc-link capacitor current ripple to improve the capacitor lifetime. In this article, the proposed method is discussed via a comparison with conventional space-vector pulsewidth modulation in full modulation index range. The modulation index range is divided into two regions, namely medium-vector modulation and hybrid modulation region. The capacitor lifetime is evaluated by the capacitor lifetime model according to the modulation methods and modulation regions. The effectiveness of the proposed modulation method is verified through simulation and experimental results.
Keywords: Active neutral point clamped; Dc link capacitor; Hybrid modulation; Lifetime improvement; Modulation methods; Power conversion systems; Space vector pulse width modulation; Thermo-mechanical damages; Active neutral-point-clamped; capacitor lifetime; dc-link current ripple; reliability; silicon carbide